EFFECT OF EXTRACTION SYSTEM AND REFINING ON THE STEROL COMPOSITION OF POMACE-OLIVE OILS - ESSID, Kamel; TRABELSI, Mahmoud; FRIKHA, Mohamed Hédi (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Research has been carried out to ascertain the effects of refining and different processing systems on the sterol compositions of pomace-olive oils and especially on the Î”-7-stigmastenol. The International Olive Council imposes limits or ranges for each type of sterol based on the natural levels found in traditional olive oil varieties. The required sterol profile (as % of total sterols) is for the âˆ†-7-stigmastenol 0.5%. A high content of this compound is non-in compliance with the International Olive Oil Standards and is at the origin of major problems at the level of the exportation because it gives the impression of the presence of seed oil in this olive oil. The sterol composition of the refined pomace-olive oils is non-in conformity with these international standards, because the percentage of Î”-7-stigmastenol exceeds slightly the tolerated limits. This percentage is more important mainly when extraction of oil is with the continuous chain. In refining, the neutralization step is with soda. The content of this compound remain invariable after neutralization by lime.